Drama and politics in the Atlantis story - Bartninkas, Vilius (Literatūra, 2019)
This paper explores the prevailing readings of the Atlantis story. The purpose of this paper is to show how interpretative judgements on the narrator’s intentions, the objectives of the characters, and the genre and the development of the story prepares the grounds for the political understanding of Athens and Atlantis. In this way, I will show how the dramatic framework influences the expression of political thought. I argue that the most important dramatic feature of the story is Critias’ interaction with Socrates and Timaeus, which explains why Critias composes two speeches that are essentially dedicated to the question of political origins.